2017
DOI: 10.2147/ppa.s128665
|View full text |Cite
|
Sign up to set email alerts
|

Persistence with golimumab in immune-mediated rheumatic diseases: a systematic review of real-world evidence in rheumatoid arthritis, axial spondyloarthritis, and psoriatic arthritis

Abstract: PurposeIn immune-mediated rheumatic diseases (IMRDs), persistence to treatment may be used as a surrogate marker for long-term treatment success. In previous comparisons of persistence to tumor necrosis factor α inhibitors (TNFis), a paucity of data for subcutaneous (SC) golimumab was identified. The aim of this study was to conduct a systematic review of persistence to SC golimumab in clinical practice and contextualize these data with five-year persistence estimates from long-term open-label extension (OLE) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 42 publications
5
27
0
1
Order By: Relevance
“…Factors for which no significant differences were found included smoking status and disease duration. The TNFi‐IR finding is consistent with previous studies in which increased drug survival with golimumab for TNFi‐naïve patients has been observed and seems to be generalizable to many bDMARDs in RA. Similar to the results for tofacitinib, high BMI has previously been reported as a predictor for discontinuation of etanercept treatment in RA .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Factors for which no significant differences were found included smoking status and disease duration. The TNFi‐IR finding is consistent with previous studies in which increased drug survival with golimumab for TNFi‐naïve patients has been observed and seems to be generalizable to many bDMARDs in RA. Similar to the results for tofacitinib, high BMI has previously been reported as a predictor for discontinuation of etanercept treatment in RA .…”
Section: Discussionsupporting
confidence: 91%
“…In a retrospective study, persistence of RA therapy (2‐year drug survival) was higher for tumor necrosis factor inhibitors (TNFis) than conventional synthetic DMARDs (csDMARDs; 38.7% and 29.5%, respectively) . A systematic review of studies from clinical practice indicated that the persistence of golimumab therapy (2‐year drug survival rates ranging from 40% to 77%) may be higher than for other TNFis . In a longitudinal observational study of patients with RA receiving bDMARDs between 1999 and 2013, discontinuations were mainly due to AEs (45.8%) and lack of efficacy (40.8%) .…”
Section: Introductionmentioning
confidence: 99%
“…GOL served as the anchor point in this analysis because a recent review concluded that GOL might be associated with higher persistence rates in a real-world setting [25]. …”
Section: Methodsmentioning
confidence: 99%
“…In patients with RA who had experienced failure on other anti-TNFα agents, the 5-year retention rate for golimumab was approximately 40% [11]. Studies in a real-world setting have also indicated a high probability of persistence with golimumab treatment in patients with RA, axial SpA or PsA, with 3-year retention rates generally around 60% when it was used as the first biological drug and 50-60% when it was given as second-line biological treatment [12,13].…”
Section: Introductionmentioning
confidence: 99%